Comparison of the Two Bath Two Stage Dyeing Method with One Bath Two Stage on Energy Efficiency in Dyeing Polyester-Cotton Fabric (80% - 20%) Using Dispersion-Reactive Dyes - Kurniawan, Kurniawan; Tantowi, Tantowi (Universitas Insan Cendekia Mandiri, 2025)
The efficiency of the dyeing process is widely used by the textile industry today to reduce production costs while maintaining the quality of the products produced. The dyeing process carried out for polyester-cotton blend fabrics (80% -20%) generally uses a two bath two stage dyeing method using disperse-reactive dyes. This dyeing process results in the dyeing process taking longer and using a lot of resources such as energy and water. In the one bath two stage method the process is faster because only one dyeing solution is used to dye the polyester-cotton at the same time with two fixation stages. Experiments were carried out on polyester-cotton fabric (80%-20%) using a disperse dye (Coralene Blue 2RL) – reactive (Corazol Brill Blue RN). The color maturity value (K/S) for fabric resulting from the two bath two stage dyeing method is 1.1138 while the one bath two stage method reaches 1.1116. The standard deviation value (evenness of color) of fabric resulting from the two bath two stage dyeing method is 0.08 while the one bath two stage method is 0.05. Color fastness to washing and rubbing using the two bath two stage method and the one bath two stage method both have good fastness.. Based on the economic aspect, the one bath two stage method provides savings in terms of dyeing time of up to 17.64% and water usage savings of up to 50% compared to the two bath two stage method. However, the total cost of the two bath two stage dyeing method has a lower total cost, namely IDR IDR 839,223.47. Meanwhile, the one bath two stage method has a total cost of IDR 875,183.25. This cost is for dyeing 500m of fabric weighing 112.14 kg. The total cost per kilogram of fabric for the two bath two stage method is IDR 7,483.71 and one bath two stage IDR 7,804.38 with a difference of IDR 320.67.